Case report: A patient with mitochondrial neurogastrointestinal encephalomyopathy and chronic intestinal failure - Barisic, Ana; Ljubas Kelecic, Dina; Vranesic Bender, Darija; Karas, Irena; Brinar, Marko; Miletic, Vladimir; Krznaric, Zeljko (Frontiers in Nutrition, 2022)
Mitochondrial neurogastrointestinal encephalomyopathy (MNGIE) is a rare disorder commonly diagnosed in later disease stages when it prominently manifests as malnutrition. We report on a female patient diagnosed with MNGIE at the age of 36. She was severely malnourished due to loss of resorptive surface after several surgical procedures, gastrointestinal dysmotility, and small intestinal bacterial overgrowth. Therefore, early and aggressive total parenteral nutrition was introduced. Although no reports have shown that nutritional support can modify the clinical outcome, this case suggests that adequate nutritional support, particularly parenteral nutrition, supervised by an experienced nutritional team, may prolong the lifespan of patients with MNGIE.